Tamsulosin and Solifenacin : A Dynamic Duo in BPH Management - Ahmed A. Essa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Benign prostatic hyperplasia (BPH), benign prostatic enlargement (BPE), and lowerurinary tract symptoms (LUTS) are among the most prevalent urological conditions affecting agingmen. Over 30% of men above the age of 60 experience moderate to severe LUTS, often requiringmedical intervention. While the pathophysiology of BPH/BPE remains partially unclear, theandrogen receptor pathway—particularly the role of dihydrotestosterone—is well established. Agentssuch as finasteride and dutasteride target this pathway by inhibiting 5α-reductase. More recently,metabolic dysfunction and chronic prostatic inflammation have also been recognized as contributingfactors to the progression of BPE and LUTS. A deeper understanding of these mechanisms is criticalfor developing more effective therapeutic strategies. This study aimed to evaluate the effectiveness ofdual therapy with tamsulosin and solifenacin in improving urinary symptoms and bladder function inpatients diagnosed with BPH. A total of 120 patients with bothersome urinary symptoms wereenrolled. Data was collected using a structured medical questionnaire, and the follow-up periodranged from 3 to 6 months. The findings demonstrated a significant improvement in symptomseverity, with the mean score decreasing from 10.09 to 3.44 post-treatment. Additionally, the pre-void urine volume increased from 181.62 ml to 260.81 ml, indicating enhanced bladder capacity.However, no statistically significant change was observed in post-void residual urine volume. Theseresults support the incorporation of tamsulosin-solifenacin dual therapy into clinical protocols formanaging LUTS in BPH patients, particularly for those with storage-related symptoms.